2010
DOI: 10.1287/isre.1100.0325
|View full text |Cite
|
Sign up to set email alerts
|

Research Commentary— Long Tails vs. Superstars: The Effect of Information Technology on Product Variety and Sales Concentration Patterns

Abstract: The Internet and related information technologies are transforming the distribution of product sales across products, and the effects are likely to grow in coming years. Both the Long Tail and the Superstar effect are manifestations of these changes, yet researchers lack consistent metrics or models for integrating and extending their insights and predictions. In this paper, we begin with a taxonomy of the technological and non-technological drivers of both the Long Tails and Superstars and then define and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 18 publications
5
123
0
7
Order By: Relevance
“…Brynjolfsson et al [10] note that Amazon.com can easily afford the consumer access to approximately 2.3 million books in print, contrasted with approximately 40,000 to 100,000 books stocked in a typical large high street store [10]. There is also cause to believe that consumers may develop a 'taste' for niche products which may be further developed by producers of these products realising the scope for further sales and further development of 'niche-supporting' technologies such as search tools and recommendation tools [11]. These might feasibly lead to an even longer long tail with a wider spread of sales of obscure titles.…”
Section: Range and The Long Tailmentioning
confidence: 99%
“…Brynjolfsson et al [10] note that Amazon.com can easily afford the consumer access to approximately 2.3 million books in print, contrasted with approximately 40,000 to 100,000 books stocked in a typical large high street store [10]. There is also cause to believe that consumers may develop a 'taste' for niche products which may be further developed by producers of these products realising the scope for further sales and further development of 'niche-supporting' technologies such as search tools and recommendation tools [11]. These might feasibly lead to an even longer long tail with a wider spread of sales of obscure titles.…”
Section: Range and The Long Tailmentioning
confidence: 99%
“…In that respect, the distribution of product sales is changing due to the increment of product assortment available to consumers (Brynjolfsson, Hu, and Smith 2010a). Actually, the Long Tail phenomenon is a manifestation of such transformations (Anderson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research methodology Brynjolfsson, Hu, and Smith (2010a) made in their paper a review of the literature about the Long Tail. They found that the Long Tail could be defined and measured in three different ways: (1) Absolute Long Tail (2), Relative Long Tail and (3) exponent based, 'because the ordinal rank to cardinal sales relationship often follows a power-law distribution, the exponent provides an indication of the relative importance of the head versus the tail of the sales distribution'.…”
Section: Introductionmentioning
confidence: 99%
“…Brynjolfsson et al, present supply and the demand-side factors that may drive the Long Tail effect [4,5]. Meanwhile Elberse and…”
Section: Introductionmentioning
confidence: 99%